The Peripheral Nervous System in Amyotrophic Lateral Sclerosis: Opportunities for Translational Research - Gentile, Francesco; Scarlino, Stefania; Falzone, Yuri Matteo; Lunetta, Christian; Tremolizzo, Lucio; Quattrini, Angelo; Riva, Nilo (Frontiers in Neuroscience, 2019)
ABSTRACT Although amyotrophic lateral sclerosis has been considered as a disorder of the motor neuron cell body, recent evidences show the non-cell-autonomous pathogenic nature of the disease. Axonal degeneration, loss of peripheral axons and destruction of nerve terminals are early events in the disease pathogenic cascade, anticipating motor neuron degeneration and the onset of clinical symptoms. Therefore, although Amyotrophic lateral sclerosis and peripheral axonal neuropathies should be differentiated in clinical practice, they also share damage to common molecular pathways, including axonal transport, RNA metabolism and proteostasis. Thus, an extensive evaluation of the molecular events occurring in the peripheral nervous system could be fundamental to understand the pathogenic mechanisms of amyotrophic lateral sclerosis, favouring the discovery of potential disease biomarkers and new therapeutic targets.